# If un = cosnθ + sinnθ, then prove that 2u6 – 3u4 + 1 = 0

• Last Updated : 12 Jan, 2022

Trigonometry is a discipline of mathematics that studies the relationships between the lengths of the sides and angles of a right-angled triangle. Trigonometric functions, also known as goniometric functions, angle functions, or circular functions, are functions that establish the relationship between an angle to the ratio of two of the sides of a right-angled triangle. The six main trigonometric functions are sine, cosine, tangent, cotangent, secant, and cosecant.

Trigonometric angles are the Angles defined by the ratios of trigonometric functions. Trigonometric angles represent trigonometric functions. The value of the angle can be anywhere between 0-360°.

Right-angled Triangle

As given in the above figure in a right-angled triangle:

• Hypotenuse: The side opposite to the right angle is the hypotenuse, It is the longest side in a right-angled triangle and opposite to the 90° angle.
• Base: The side on which angle C lies is known as the base.
• Perpendicular: It is the side opposite to angle C in consideration.

### Trigonometric Functions

Trigonometry has 6 basic trigonometric functions, they are sine, cosine, tangent, cosecant, secant, and cotangent. Now let’s look into the trigonometric functions. The six trigonometric functions are as follows,

1. sine: the ratio of perpendicular and hypotenuse is defined as sine and It is represented as sin θ
2. cosine: the ratio of base and hypotenuse is defined as cosine  and it is represented as cos θ
3. tangent: the ratio of sine and cosine of an angle is defined as tangent. Thus the definition of tangent comes out to be the ratio of perpendicular and base and is represented as tan θ
4. cosecant: It is the reciprocal of sin θ and is represented as cosec θ.
5. secant: It is the reciprocal of cos θ and is represented as sec θ.
6. cotangent: It is the reciprocal of tan θ and is represented as cot θ.

According to the above image, Trigonometric Ratios are

1. sin θ = Perpendicular / Hypotenuse = AB/AC
2. cosine θ = Base / Hypotenuse = BC / AC
3. tangent θ = Perpendicular / Base = AB / BC
4. cosecant θ = Hypotenuse / Perpendicular = AC/AB
5. secant θ = Hypotenuse / Base = AC/BC
6. cotangent θ = Base / Perpendicular = BC/AB

### Reciprocal Identities

sin θ = 1/ cosec θ                     OR                 cosec θ = 1/ sin θ

cos θ = 1/ sec θ                       OR                sec θ = 1 / cos θ

cot θ = 1 / tan θ                     OR                tan θ = 1 / cot θ

cot θ = Cos θ / sin θ               OR               tan θ = sin θ / cos θ

tan θ.cot θ = 1

### Values of Trigonometric Ratios

Trigonometric Identities of Complementary and Supplementary Angles

• Complementary Angles: Pair of angles whose sum is equal to 90°.

Identities of Complementary angles are:

sin (90° – θ) = cos θ

cos (90° – θ) = sin θ

tan (90° – θ) = cot θ

cot (90° – θ) = tan θ

sec (90° – θ) = cosec θ

cosec (90° – θ) = sec θ

• Supplementary Angles: Pair of angles whose sum is equal to 180°.

Identities of supplementary angles are:

sin (180° – θ) = sin θ

cos (180° – θ) = – cos θ

tan (180° – θ) = – tan θ

cot (180° – θ) = – cot θ

sec (180° – θ) = – sec θ

cosec (180° – θ) = – cosec θ

### Solution:

Here we have:

un  = cosnθ+sinnθ

To prove : 2u6 – 3u4 + 1 = 0

Lets n = 6

So, un  = cosnθ+sinnθ

u6 = cos6θ+sin6θ

u6 = (cos2θ)3+ (sin2θ) 3

u6 = (cos2θ +sin2θ)3− 3(cos 2θ)(sin 2θ)(cos 2θ+sin 2θ)

u6 =1−3cos2θ sin2θ                                                                                         ……. (1)                                                   { cos2θ +sin2θ = 1 }

Now let n = 4

u4 = cos4θ + sin4θ

u4​  = (cos2θ)2 + (sin2θ)2

u4 = (cos2θ + sin2θ) 2−2(cos 2θ)(sin 2θ)                                                                                                                      { cos2θ +sin2θ = 1 }

u4​  = 1− 2cos2θsin2θ                                                                                 ……. (2)

Now to prove

2u6 – 3u4 + 1 = 0

Put values from equations (1) and (2).

So,

2u6 – 3u4 + 1 = 0

= 2(1−3cos 2θ sin 2θ) − 3(1−2cos 2θsin 2θ)+1

= 2 − 6cos2θ sin2θ − 3 + 6cos2θ sin2θ)+1

= 2 -3 +1

=

Therefore  2u6 – 3u4 + 1 = 0

Hence proved

### Similar Questions

Problem 1:  If cos θ + sin θ = √2 cos θ, prove that cos θ – sin θ = √2 sin θ?

Solution:

Here we have

cos θ + sin θ = √2 cos θ

Squaring both the sides

(cos θ + sin θ)2 = (√2 cos θ)2

cos2 θ + sin2 θ + 2 sin θcos θ = 2 cos 2θ

cos2 θ – sin2 θ = 2 sin θcos θ

(cos θ + sin θ)(cos θ – sin θ) = 2 sin θcos θ

(cos θ – sin θ) = 2 sin θcos θ/(cos θ + sin θ)

cos θ – sin θ = 2 sin θcos θ/√2 cos θ               {cos θ + sin θ = √2 cos θ}

cos θ – sin θ = √2 sin θ

Hence proved

Problem 2: Prove that (cos θ sec θ)/cot θ = tan θ.

Solution:

Here we have

cos θ sec θ / cot θ = tan θ

Therefore,

{ cos θ sec θ }/ cot θ = tan θ

By taking L.H.S

cos θ sec θ / cot θ

we can write cos θ sec θ as 1

= (cos θ sec θ )/cot θ

= 1/cot θ                                                                                                                              {cos θ = 1/ sec θ   therefore Cos θ Sec θ  = 1}

= tan θ                                                                                                                                 {tan θ = 1 / cot θ }

Therefore LHS = RHS

{cos θ sec θ}/ cot θ = tan θ

Hence Proved

Problem 3 : prove {(cot A + cosec A – 1) / (cot A – cosec A + 1)} = {(1 + cos A) / sin A} ?

Solution:

We have

To prove : {(cot A + cosec A – 1) / (cot A – cosec A + 1)} = {(1 + cos A) / sin A}

First LHS = {(cot A + cosec A – 1) / (cot A – cosec A + 1)}

= {(cot A + cosec A ) – ( cosec2 A – cot2A ) } / {(cot A – cosec A) + 1}          { cosec2 A – cot2A = 1 }

=  {( cosec A + cot A ) –  ( cosec A + cot A )( cosec A – cot A ) } / (cot A – cosec A + 1 )

=  {( cosec A + cot A ) [ 1 – ( cosec A – cot A ) ] } / (cot A – cosec A + 1 )

=  {( cosec A + cot A ) ( cot A – cosec A  + 1 )} / (cot A – cosec A + 1 )

=    cosec A + cot A

=   (1 / sin A) + (cos A / sin A)

=  (1 + cos A) / sin A

RHS
Hence Proved

Problem 4 : If sin θ + cos θ  = √2 , then prove tan θ  + cot θ  = 2

Solution:

We have sin θ + cos θ  = √2

Squaring both sides

(sin θ + cos θ)2  = (√2 )2

sin2 θ + cos2 θ  + 2 sin θcos θ = 2

1 + 2 sin θcos θ = 2                                                                                                                                             {sin2 θ + cos2 θ = 1}

2 sin θcos θ = 2 – 1

2 sin θcos θ = 1

2 sin θcos θ = sin2 θ + cos2 θ

Divide both sides by sin θcos θ

2 sin θcos θ / sin θcos θ = (sin2 θ + cos2 θ) / sin θcos θ

2 = (sin2 θ / sin θcos θ) + (cos2 θ / sin θcos θ)

2 = (sin θ / cos θ) + (cos θ / sin θ)

2 = tan θ  + cot θ

Hence proved, tan θ  + cot θ  = 2.

My Personal Notes arrow_drop_up